Clinical management of intestinal failure - Duggan, Christopher; Jaksic, Tom.; Gura, Kathleen M. (Boca Raton : Taylor & Francis, 2012)
'This reference provides a current, multidisciplinary approach to the care of patients with intestinal failure. It includes intensive discussion on medical and nutritional issues especially relative to children with intestinal failure. It presents information on transplantation, but emphasizes rehabilitation. Topics cover etilogy/epidemiology, pathophysiology, and clinical assessment of intestinal failure in adults and pediatrics; medical and surgical management; prevention and treatment of complications of intestinal failure; nursing management; emerging diagnostic and therapeutic methods; and long term care. It is written by experts in nutrition, gastroenterology and pediatrics, pharmacy, as well as gastrointestinal surgery'--
Book is accompanied by one CD-ROM bearing the same call number and available at Makmal Digital, Perpustakaan Dr. Abdul Latiff, KKL.
Book is accompanied by one CD-ROM'Clinical management of intestinal failure' bearing the same call number and available at Koleksi Media, Perpustakaan PPUKM.
Includes bibliographical references and index.
Keywords: Malabsorption syndromes; Fat -- Metabolism